Prevailing challenges in Processing of Fermented Fishery product ‘Shidal’ in Tripura, India and Solutions - Uchoi, Devananda; Kishore, Pankaj; Kumar, Anuj; Nadella, Ranjit Kumar; Panda, Satyen Kumar; Zynudheen, A. A. (Fishery Technology, 2022)
Shidal is a traditionally bio-processed fermented fishery product produced from minor carps particularly, Puntius sp. It plays a significant role in the diet of North-Eastern people in India. In Tripura and other North-Eastern states, shidal is consumed as health food by general public. Hygienic processing of shidal has received more attention in recent years as the number of consumers and demand for superior quality shidal is increasing. The study was undertaken in 14 dry fish markets from 4 districts of Tripura through market survey and personal interview to identify key challenges associated with processing of shidal. Data was collected from a total of 50 randomly selected respondents from commercial shidal processors (n=10), household shidal processors (n=10), retailers (n=20) and local vendors (n=10). It was found that for commercial shidal processors, supply of poor quality raw materials and lack of skilled workers were the major issues. In case of household processors, lack of adequate infrastructure and breakage of earthen pots were the main issues; whereas, for retailers and street vendors lack of proper packaging system was the main issue. Thus, the challenges in shidal processing were recorded and solutions are suggested which could help the policy makers to recommend guidelines for hygienic handling and processing of shidal.